Hubungan Literasi Digital dengan Self Direct Learning pada Mahasiswa di Daerah Miskin Sumatera - Novanda, Ridha Rizki (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2019)
Searching for lecture materials through digital media is more widely used compared to conventional media. Information literacy means being able to evaluate and combine information. The rapid development of information technology now requires students to be able to follow it. However, with a poverty percentage of 16.45%, Bengkulu Province has a more significant challenge to catch up. It is important to analyze how the relationship between digital information literacy and self-direct learning for students in weak areas of the Sumatra islands. The study was conducted in May 2018 with respondents as many as 100 students. Data processing is done by using rank spearman to see the relationship between information literacy and selfdirect learning. Based on the results of the study, identifying information is significantly related to learning to self-manage. Furthermore, evaluating information sources is significantly related to students thinking independently. While other factors are not related.